Aspectos Conceptuales de la Justicia Climática - Costa, Hirdan (2021)
The theme of climate change has several ramifications in law, starting with the concepts that involve justice. Along these lines, the objective of this article is to address the meaning of climate justice. The methodology is analytical and qualitative, using literature review methods. The results demonstrate that the origins of climate justice are correlated to environmental justice, therefore, it has four essential aspects for its understanding: distributive justice, procedural justice, justice by recognition, corrective justice, and social justice. The final considerations weave the difficulties for the application of measures that aim at effecting climate justice and draws attention to the challenges that cover the consequences resulting from climate changes.